NK Cells and PMN-MDSCs in the Graft From G-CSF Mobilized Haploidentical Donors Display Distinct Gene Expression Profiles From Those of the Non-Mobilized Counterpart - Pelosi, Andrea; Besi, Francesca; Tumino, Nicola; Merli, Pietro; Quatrini, Linda; Li Pira, Giuseppina; Algeri, Mattia; Moretta, Lorenzo; Vacca, Paola (Frontiers in Immunology, 2021)
A recent approach of hematopoietic stem cell (HSC) transplantation from haploidentical donors “mobilized” with G-CSF is based on the selective depletion of αβ T and B lymphocytes from the graft. Through this approach, the patient receives both HSC and mature donor-derived effector cells (including NK cells), which exert both anti-leukemia activity and protection against infections. We previously showed that donor HSC mobilization with G-CSF results in accumulation in the graft of polymorphonuclear myeloid-derived suppressor cells (PMN-MDSC), capable of inhibiting in vitro the anti-leukemia activity of allogeneic NK cells. Here, we performed a detailed gene expression analysis on NK cells and PMN-MDSC both derived from mobilized graft. Cytotoxicity assays and real time PCR arrays were performed in NK cells. Microarray technology followed by bioinformatics analysis was used for gene expression profiling in PMN-MDSC. Results indicate that NK cells from the graft have a lower cytolytic activity as compared to those from non-mobilized samples. Further, mobilized PMN-MDSC displayed a peculiar transcriptional profile distinguishing them from non-mobilized ones. Differential expression of pro-proliferative and immune-modulatory genes were detected in mobilized PMN-MDSC. These data strengthen the concept that G-CSF-mobilized PMN-MDSC present in the graft display unique molecular characteristics, in line with the strong inhibitory effect on donor NK cells.